Twentieth century dust lows and the weakening of the westerly winds over the Tibetan Plateau. Issue 7 (14th April 2015) - Grigholm, B.; Mayewski, P. A.; Kang, S.; Zhang, Y.; Morgenstern, U.; Schwikowski, M.; Kaspari, S.; Aizen, V.; Aizen, E.; Takeuchi, N.; Maasch, K. A.; Birkel, S.; et al.
Abstract Understanding past atmospheric dust variability is necessary to put modern atmospheric dust into historical context and assess the impacts of dust on the climate. In Asia, meteorological data of atmospheric dust is temporally limited, beginning only in the 1950s. High‐resolution ice cores provide the ideal archive for reconstructing preinstrumental atmospheric dust concentrations. Using a 500 year (1477–1982 A.D.) annually resolved calcium (Ca) dust proxy from a Tibetan Plateau (TP) ice core, we demonstrate the lowest atmospheric dust concentrations in the past 500 years during the latter twentieth century. Declines in late nineteenth to twentieth century Ca concentrations significantly correspond with regional zonal wind trends from two reanalysis models, suggesting that the Ca record provides a proxy for the westerlies. Twentieth century warming and attendant atmospheric pressure reductions over northern Asia have potentially reduced temperature/pressure gradients resulting in lower zonal wind velocities and associated dust entrainment/transport in the past 500 years over the TP.